GE_GERICHTE A/1795/2021 vom 7. März 2022 - GE Cour de justice (2022)
DÉDUCTION DES FRAIS D'ACQUISITION(DROIT FISCAL);IMPÔT;CARRIÈRE | LIFD.32.al2; LIFD.32.al4; LIPP.34.letd; LIFD.34.lete; LIPP.38.lete